2020
DOI: 10.1177/1524838020906533
|View full text |Cite
|
Sign up to set email alerts
|

Nonconsensual Porn as a Form of Intimate Partner Violence: Using the Power and Control Wheel to Understand Nonconsensual Porn Perpetration in Intimate Relationships

Abstract: Over the last decade, nonconsensual porn (NCP), or the sharing of sexually explicit material without a person’s consent, has become a growing problem with potentially far-reaching adverse consequences for victims. The purpose of this article is to propose and consider a framework for advancing the field’s understanding of NCP within the context of intimate relationships including situating NCP relative to other forms of relational abuse. Specifically, we examined the extent to which NCP in intimate partner rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 53 publications
(70 reference statements)
2
50
0
Order By: Relevance
“…This review recognized NCP as a form of gender-based violence that should be considered on a continuum of sexual abuse (Walker & Sleath, 2017). Consistent with this depiction, one psychological framework used to understand NCP was the Power and Control Wheel (Eaton et al, 2020), which describes tactics abusers employ to maintain power and control over victims. In an analysis of 5 years of published U.S. news articles on NCP, Eaton and colleagues (2020) concluded that NCP has been perpetrated in intimate relationships using all eight of the abuse metatactics in the Power and Control Wheel, with the three most common being emotional abuse, coercion and threats, and denial/blame/minimization.…”
Section: Review Of Psychology Literature On Nonconsensual Pornmentioning
confidence: 99%
“…This review recognized NCP as a form of gender-based violence that should be considered on a continuum of sexual abuse (Walker & Sleath, 2017). Consistent with this depiction, one psychological framework used to understand NCP was the Power and Control Wheel (Eaton et al, 2020), which describes tactics abusers employ to maintain power and control over victims. In an analysis of 5 years of published U.S. news articles on NCP, Eaton and colleagues (2020) concluded that NCP has been perpetrated in intimate relationships using all eight of the abuse metatactics in the Power and Control Wheel, with the three most common being emotional abuse, coercion and threats, and denial/blame/minimization.…”
Section: Review Of Psychology Literature On Nonconsensual Pornmentioning
confidence: 99%
“…recording and sharing of their sexual interactions are vulnerable for consent violations in the form of wide circulation of the material against their will (so-called "revenge porn"; Eaton et al, 2020) or consent violations in the form of pressured or unwanted activities in front of the camera (Boyle, 2011).…”
Section: Producing Digital Media Content During Face-to-face Sexual Interactionsmentioning
confidence: 99%
“…Some individuals and couples digitally document and share their sexual activities just out of curiosity and fun ( Schwarz, 2010 ), while others do it with commercial interest in a more or less professionalized form ( Hofer, 2014 ), still trying to express authenticity ( Stardust, 2019 ). Users involved in either non-commercial or commercial digital recording and sharing of their sexual interactions are vulnerable for consent violations in the form of wide circulation of the material against their will (so-called “revenge porn”; Eaton et al, 2020 ) or consent violations in the form of pressured or unwanted activities in front of the camera ( Boyle, 2011 ).…”
Section: Sexual Interaction Through Digital Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Revenge porn affects women at higher rates than men, with one study by the Cyber Civil Rights Initiative finding that women were 1.5 times more likely to be victims of revenge porn than men. 14 Nonconsensual pornography is "the distribution of sexually graphic images of individuals without their consent … as well as images originally obtained with consent, usually within the context of a private or confidential relationship." 15 Revenge porn is a phrase often used interchangeably with nonconsensual pornography.…”
mentioning
confidence: 99%